Accumulation and potential sources of lead in marine organisms from coastal ecosystems of the Chilean Patagonia and Antarctic Peninsula area. (March 2019) - Espejo, Winfred; Padilha, Janeide de A.; Gonçalves, Rodrigo A.; Dorneles, Paulo R.; Barra, Ricardo; Oliveira, Douglas; Malm, Olaf; Chiang, Gustavo; Celis, José E.
Abstract: Environmental concentrations of Pb have been increased due to anthropogenic activities, which have provoked the released of this element to the environment in large amounts. To understand how Pb behaves in remote southern marine ecosystems, we measured Pb concentrations and isotope ratios in biota from coastal marine ecosystems of the Chilean Patagonia and the Antarctic Peninsula area. Lead concentrations in the aquatic organisms ranged from 0.02 to 1.19 mg kg −1 d.w. In Patagonia, higher Pb levels were found in fish than in invertebrates (crab, shrimp, porifera, limpet and shellfish). In comparison with the baseline reference values from other parts of the world, fishes exhibited lower Pb levels. The results of Pb isotopic compositions indicated that the bioaccumulation of Pb in marine organisms come from different anthropogenic sources. These Pb levels might be useful for further studies that allow a deeper evaluation of sources for Pb contamination in these remote ecosystems. Highlights: Lead was measured in tissues of macroinvertebrates and fishes from Patagonia and Antarctica. Lead concentrations in the aquatic organisms are lower than those measured at lower latitudes. Pb in marine ecosystems studied are due mainly to anthropogenic activities instead of natural sources.